Milk molars or extra premolars in Mesotheriinae (Mesotheriidae, Notoungulata): New insights into an old controversy - Cerdeño Serrano, Maria Esperanza (2013)
A recently recovered specimen of Mesotheriinae (Mesotheriidae, Notoungulata) from the late Miocene-early Pliocene of La Rioja Province (Argentina), CRILAR Pv 433, corresponds to an individual with three upper premolars, which appears to be an "anomaly" among mesotheriines. The detailed study of this specimen, however, brings up an old controversy on the interpretation of different mesotheriine specimens with three upper or two lower premolars. After being described as different taxa, these were later considered to be juvenile representatives of other known species. The three upper or two lower teeth were interpreted as the milk molars DP2-4 and dp3-4, respectively, which would be replaced in adult life just for two upper (P3-4) and one lower (p4) permanent premolars. The new material leads us to set up a different interpretation. In our opinion, all these specimens actually preserve the permanent dentition, corresponding to different ontogenetic stages of more or less young individuals. This consideration implies the necessity of a deep systematic revision of the whole subfamily keeping in mind this new point of view and the ontogenetic variation within a species. Therefore, the presence of P2/p3 is not enough to define a different taxon at this moment. Pending this taxonomic revision, the dental morphology of CRILAR Pv 433 resembles both Typotheriopsis (e.g., upper premolars with one labial sulcus) and Pseudotypotherium (e.g., P4 with lingual groove, wide median lobe of M3) as these two Late Miocene genera are currently characterized. Furthermore, P2/p3 could be expelled soon in the lifetime of individuals, and even the presence of P2/p3 could be a variable character within the same taxon; if so, this might reflect an evolutionary trend to the loss of a dental element within mesotheriines, but the revision of a large sample is necessary to support or reject these hypotheses.